English Listening Anxiety of Indonesian Speakers - Candrika Citra Sari; Rindawati Rindawati (English Department FBS UNP, 2021)
Research on foreign language anxiety among Indonesian learners of English has gained some attention thus far. However, few studies have examined specifically English listening anxiety of Indoensian speakers. Previous research in other countries has suggested a number of variables contributing to the foreign language anxiety. Taking into consideration some of the factors that are distinctive for Indonesian learners’ contexts, this present study aims to find out the relationship between number of languages learned or acquired by the learners, gender of the learners, the learners’ English self-rating proficiency, and length of residence of the learners in the target language country with L2 listening anxiety of Indonesian learners of English. This study involved Foreign Language Listening Anxiety Scale (FLLAS) data that were obtained from 109 Indonesian university students and were analyzed quantitatively using Pearson’s correlation, Spearman’s rho, and one-way ANOVAs. The finding shows that there is a significant negative correlation between Indonesian learners of English listening anxiety with the learners’ length of residence in the target language country and the learners’ English self-rating proficiency. The significant difference in terms of length of residence in the target language country especially lied in between the no residence group and <1-year group, and between no residence group and >1 year. In the English self-rating, the significant difference lied in between Intermediate and advanced groups.